PENGARUH KUALITAS PRODUK, PROMOSI, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN AIR MINERAL NESTLE PURE LIFE - Yolanda, Yola; Tarigan, Purnaya Sari; Pertiwi, Suci (POLITEKNIK LP3I JAKARTA, 2025)
This research aims to acknowledge and analyze The Influence of Product Quality, Promotion, and Price on Purchasing Decisions for Nestlé Pure Life Mineral Water Products among Accounting Study Program Students at Prima Indonesia University (UNPRI) in Medan. The sampling technique in this research used Accidental Sampling by distributing questionnaires online using Google Forms to 100 samples, which are all consumers of Nestlé Pure Life Mineral Water. The data analysis method used in this research is multiple linear regression analysis. As the result shows, partially Product Quality and Price have no significant effect on Purchasing Decisions, while Promotion has a significant effect on Purchasing Decisions. Simultaneously shows that Product Quality, Promotion, and Price have a significant effect on Purchasing Decisions. The coefficient of determination (Adjusted R Square) value obtained is 53% and the remaining 47% is influenced by other factors not examined in this research